Optimizing profitability through leaf and seed yields of vegetable mustard (Brassica juncea L.): OPTIMIZING PROFITABILITY THROUGH LEAF AND SEED YIELDS OF VEGETABLE MUSTARD - ABDUR RAHIM; J C JANA (Journal of Oilseeds Research, 2025)
A field experiment was conducted during 2022-23 and 2023-24 rabi seasons to optimize sowing time, plant spacing and leaf cutting frequency for maximizing profitability through leaf and seed yield in vegetable mustard (Brassica juncea L.) cv. Pusa Sag-1. The study employed a three-factorial randomized block design with two sowing dates (mid-September and mid-October), three plant spacings (30 cm × 10 cm, 30 cm × 20 cm, and 30 cm × 30 cm), and three leaf cutting frequencies (no cutting, one cutting, and two cuttings). Mid-October sowing significantly increased seed yield (11.13 q/ha) by 8.80% compared to mid-September sowing. The closest spacing (30 cm × 10 cm) produced maximum seed yield (12.50 q/ha) and leaf yield (10.19 t/ha), representing 32.98% and 136.43% increases over widest spacing, respectively. No leaf cutting resulted in highest seed yield (12.10 q/ha), while two cuttings maximized leaf yield (14.54 t/ha). The interaction between mid-October sowing and 30 cm × 10 cm spacing yielded maximum seed production (14.97 q/ha), while 30 cm × 10 cm spacingwith two leaf cuttings produced highest leaf yield (21.59 t/ha) and benefit-cost ratio (4.53). Results demonstrate a trade-off between leaf harvest frequency and seed production, with strategic agronomic management enabling optimization of dual-purpose cultivation in vegetable mustard.